OUTPATIENT WAITING TIME IN INTERNAL MEDICINE: LEAN SIX SIGMA ROOT-CAUSE ANALYSIS WITH PROPOSED AI INTERVENTIONS - Bobby Hery Yudhanto; Elsye Maria Rosa; Anna Surgean Veterini; Rizky Fajar Meirawan (Pena Cendekia Insani, 2026)
Outpatient waiting time is a critical service-quality indicator in Indonesian hospitals. At Hospital X, Sidoarjo, the Internal Medicine Clinic's average wait time reached 83 minutes and 58 seconds, approximately 40% above the 60-minute standard. This qualitative study applies in-depth interviews, fishbone analysis, and Lean Six Sigma (LSS) to identify root causes and formulate improvement recommendations. Findings identify systemic waste and defects, including complex B1–B6 clinical assessments, electronic medical record (EMR) constraints, high staff workloads risking burnout, and unreliable wait-time estimates despite an effective online registration system. In the short term, implementing e-Signatures to eliminate physical documentation workflows is identified as the most immediately actionable intervention. Ambient AI Scribe and AI Predictive Analytics are proposed as longer-term, infrastructure-contingent interventions requiring contextual validation before adoption. Reducing waiting times below 60 minutes through this combined strategy is operationally plausible but remains an unvalidated projection requiring further quantitative confirmation.